Maternal Nutritional Knowledge, Clean and Healthy Living Behavior, and Posyandu Attendance as Determinants of Stunting among Children Under Five - Al Magfirah; M Noris; Nur Husnul Khatimah; Aris Irwansyah (Universitas Muhammadiyah Palembang, 2026)
Toddlers are a vulnerable group at risk of nutritional problems. One of the nutritional issues affecting toddlers is stunting. Several factors contribute to stunting, including mothers' knowledge of nutrition, Clean and Healthy Living Behavior (PHBS), and attendance at integrated health service posts (Posyandu). This study aimed to determine the relationship between mothers' nutritional knowledge, PHBS behavior, and Posyandu attendance with the incidence of stunting. This study employed an analytical observational design with a cross-sectional approach. Samples were selected using purposive sampling, involving 44 toddlers in Tarlawi Village. Stunting data were obtained through height-for-age (H/A) measurements, while data on mothers' nutritional knowledge, PHBS behavior, and Posyandu attendance were collected using questionnaires. Data were analyzed using the Chi-Square test. The results of the association analysis showed that there was no significant relationship between mothers' nutritional knowledge and stunting among children aged 24–59 months (p = 0.680 > 0.05), nor between Clean and Healthy Living Behavior (PHBS) and stunting (p = 1.000 > 0.05). However, there was a significant relationship between Posyandu attendance and stunting (p < 0.001). There was no significant relationship between mothers' nutritional knowledge and the incidence of stunting among children aged 24–59 months in Tarlawi Village. Likewise, there was no significant relationship between Clean and Healthy Living Behavior (PHBS) and the incidence of stunting among children aged 24–59 months in Tarlawi Village. However, there was a significant relationship between Posyandu attendance and the incidence of stunting among children aged 24–59 months in Tarlawi Village.